An innovative psychometric solar-powered water desalination system - Shatat, Mahmood; Riffat, Saffa; Gan, Guohui (Oxford University Press, 2016)
Important advances have been made in solar water desalination technology but their wide application is restricted by relatively high capital and running costs. Until recently, solar concentrator collectors had usually been employed to distill water in compact desalination systems. Currently, it is possible to replace these collectors by the more efficient evacuated tube collectors, which are now widely available on the market at lower prices. This paper describes the results of experimental and theoretical investigations of the operation of a novel small-scale solar water desalination technology using the psychometric humidification and dehumidification process coupled with a heat pipe evacuated tube solar collector with an aperture area of ~1.73 m2. Solar radiation during spring in the Middle East was simulated by an array of halogen floodlights. A synthetic brackish water solution was used for the tests and its total dissolved solids (TDSs) and electrical conductivity were measured. A mathematical model was developed to describe the system's operation. A computer program was written to solve the system of governing equations to perform the theoretical calculations of the humidification and dehumidification processes. The experimental and theoretical values for the total daily distillate output were found to be closely correlated. The test results demonstrate that, at temperatures of 55-60°C, the system produces ~5-6 kg/h of clean water with a high desalination efficiency. Following the experimental calibration of the mathematical model, it was demonstrated that the performance of the system could be improved to produce a considerably higher amount of fresh water.